Self-Medication in Patients with Melasma: Risk Factors and Consequences - Shams, Nadia; Zeeshan, Sumayya; Niaz, Furquana; Khan, Mahvish Aftab; Ul Islam, Nayyar; Seetlani, Naresh Kumar; Farhat, Shazia (Journal of Liaquat University of Medical & Health Sciences, 2020)
OBJECTIVE: To assess self-medication in melasma cases by examining their reasons and consequences. METHODOLOGY: This descriptive cross-sectional study included 300 melasma cases were selected by convenience sampling from outdoor Dermatology and Medicine Department Rawal Institute of Health Science Islamabad (January-June 2018). Patients already under care of dermatologist and with severe systemic illness, also, patients with underlying endocrine disease or systemic conditions leading to hyper pigmentation, cases with drug induced pigmentation and receiving oral contraceptive pills were excluded. Demographic details, self-medication type, reasons, complications and alternative therapy were documented. Data analyzed by SPSS V-17 with significant p<0.05. RESULTS: Among 300 melasma cases, 227(75.6%) reported self-medication with 213(93.8%) females and 14(6.2%) males, mean age 30+5.7 years and melasma duration 3.55+3.6 years. Superficial melasma 156 (68.8%) and deep 64(28%). Sun-block used by 29(12.8%). Oral self-medication 15(6.6%), alternative medicine 70(30.8%), mud application 42(18.5%), whitening creams 149(65.6%) and therapy by beautician 136(60%). Hospital access lack in 14(6.2%), lack of money 7(3%), distrust on doctors 3 (13.2%), perceived as minor disease 176(77.5%). Reason for consultation was no improvement in 84 (37%), partial improvement 50(22%) and worsening 93(43%). Complications observed were acne in 91(40%), skin thinning 14(6.2%) and hirsutism 44(19.4%). Associations were acid peptic disease 21(9%), family history 28(12%) and pregnancy 8(3.5%). Mean expenditure was 4,160 rupees/month. CONCLUSION: Self-medication by whitening creams and therapy by beautician is frequent among melasma cases followed by herbal therapy, mud application, oral and topical medication. Delayed presentation and associated complications of self-medication i.e. acne, hirsutism, skin thinning, folliculitis and telangiectasias need to be addressed. Authors recommend sun-block and early dermatology consultation to prevent complications, recurrence and improve quality of life.